The Usability of C++ Interactive Self-Assessment Quiz (i-SAQ) - Ibrahim, N.S.; Hasmy, H.; Kapi, A.Y.; Suhaimi, A. (International Journal of Human and Technology Interaction (IJHaTI), 2018)
The rising of technologies these days affected most of the sectors in the country including education. Traditional assessment method gives difficulty to both students and lecturers in term of learning and teaching process. Therefore, this study proposed an online quizzes application called i-SAQ (C++ Interactive Self-Assessment Quiz) which adopt formative assessment method to help students and lecturers in their learning and teaching process. The feature of i-SAQ which offers immediate feedback while answering the quiz attracts students in having a hassle-free way of discovering knowledge. This feature also helps lecturers in handling large number of students in term of giving the feedback from formative assessment. The usability test was conducted to a group of 64 students to test the functionality of i-SAQ by using questionnaire approach. From the analysis, most of the students gave highest points for every questionnaire usability factors which shows that i-SAQ is one useful and interesting learning support tool.